Image acts: a systematic approach to visual agency - Bredekamp, Horst (Image, word, action, 2018)
Heavily represented sections of contemporary philosophy subscribe to the notion of "embodiment". However promising this pragmatic turn of events may be, it remains limited in that it interprets the world as a projection of the cognizing "I". By contrast, Image Acts focuses on the counterforce of the form of images. The book subdivides this sphere into three parts: imitation, substitution, and the pure effect of the form. All three parts are contemplated with examples from antiquity through to the present and the iconoclastic controversies of our times. From this reconstruction of the image act springs the element of a new philosophy of affordance.